An Overview on G Protein-coupled Receptor-induced Signal Transduction in Acute Myeloid Leukemia - Selheim, Frode; Aasebø, Elise; Ribas, Catalina; Aragay, Anna M. (Current Medicinal Chemistry, 2019)
Background: Acute Myeloid Leukemia (AML) is a genetically heterogeneous disease characterized by uncontrolled proliferation of precursor myeloid-lineage cells in the bone marrow. AML is also characterized by patients with poor long-term survival outcomes due to relapse. Many efforts have been made to understand the biological heterogeneity of AML and the challenges to develop new therapies are therefore enormous. G Protein-coupled Receptors (GPCRs) are a large attractive drug-targeted family of transmembrane proteins, and aberrant GPCR expression and GPCR-mediated signaling have been implicated in leukemogenesis of AML. This review aims to identify the molecular players of GPCR signaling, focusing on the hematopoietic system, which are involved in AML to help developing novel drug targets and therapeutic strategies. Methods: We undertook an exhaustive and structured search of bibliographic databases for research focusing on GPCR, GPCR signaling and expression in AML. Results and Conclusion: Many scientific reports were found with compelling evidence for the involvement of aberrant GPCR expression and perturbed GPCR-mediated signaling in the development of AML. The comprehensive analysis of GPCR in AML provides potential clinical biomarkers for prognostication, disease monitoring and therapeutic guidance. It will also help to provide marker panels for monitoring in AML. We conclude that GPCR-mediated signaling is contributing to leukemogenesis of AML, and postulate that mass spectrometrybased protein profiling of primary AML cells will accelerate the discovery of potential GPCR related biomarkers for AML.
Keywords: cell signaling